Perangcangan Sistem Pengelolaan Data Nasabah Menggunakan Algoritma Knuth Morris Pratt Berbasis Web (Studi Kasus: MMS Bojong Gede BTPN Syariah) - Dian Woro Agustia; Samsoni (CV. Multi Kreasi Media, 2024)
The process of managing customer data at MMS Bojong Gede is still running simply using Ms Excel, this can cause problems when in a center there is the same customer name data. Over time the amount of customer data will change either increase or decrease, so that managing data manually is less effective, besides that each (CO) or (PS) each has an excel file in managing customer data, this makes data storage less centralized and has an impact on the process of finding customer data smoothly or in arrears. In order for operations to run efficiently, a computerized customer data management and search system is needed to integrate customer data into an integrated database, so that customer data can be managed properly. In this study, the knuth morris pratt algorithm has been applied to the system search function to maximize the search process. The results of this study are in the form of a web-based customer data management and search system, with a system that has been built the process of managing and searching customer data to be more effective and efficient, this is evidenced by the test results with the average time needed by the knuth morris pratt algorithm to find a customer data is 1.541(s).